Cryptosporidium and Giardia: challenges in public water supplies - Brisa Maria Fregonesi; Carolina de Freitas Sampaio; Mariana Frari Ragazzi; Karina Aparecida de Abreu Tonani; Susana Inés Segura-Muñoz (O Mundo da Saúde)
Water-borne diseases caused by opportunistic protozoa re-emerged as an important public health problem in recent years, despite technological advances in water treatment processes. In this context, agents such as Cryptosporidium and Giardia produce (oo)cysts resistant to conventional water treatment and can cause serious cases of morbidity in immunocompromised individuals. In Brazil, water control by specific and sensitive techniques aimed at detecting Cryptosporidium and Giardia still is not widespread. The aim of this study was to do a critical analysis of the scientific evidence on the contamination of public water supplies by Cryptosporidium and Giardia. We did a systematic review of the literature produced from 2001 to 2011 in PUBMED and LILACS databases. From the results, we find a cosmopolitan distribution of these parasites in different sources of treated water, representing a risk to public health and a challenge for environmental monitoring, considering the specificity and high cost of internationally recognized analytical techniques for identifying these pathogens in water